Thermal performance of a flat-plate solar collector using aqueous colloidal dispersions of carbon-based nanostructures / Wail Sami Wadee Sarsam - Wail Sami, Wadee Sarsam (2017)
The effects of using aqueous nanofluids containing functionalized carbon-based nanostructures as novel working fluids on the thermal performance of flat-plate solar collectors (FPSCs) have been investigated. The nanomaterials used were graphene nanoplatelets (GNPs) with specific surface areas (SSAs) of 300, 500, and 750 m2/g; and multi-walled carbon nanotubes (MWCNTs) with outside diameters of (< 8 nm) and (2030 nm). Water-based nanofluids with weight concentrations of 0.025%, 0.05%, 0.075%, and 0.1% were prepared. The thermophysical properties and colloidal stability of the nanofluids were investigated. To study the thermal performance of nanofluid-based FPSCs, an experimental setup was designed and built; and a MATLAB code was developed. Test runs were performed using inlet fluid temperatures of 30, 40, and 50 °C; flow rates of 0.6, 1.0, and 1.4 kg/min; and heat flux intensities of 600, 800, and 1000 W/m2. Higher colloidal stability was obtained at 60-min ultrasonication time. Nanofluids containing pristine nanomaterials were unstable. Non-covalent functionalization with surfactants improved the colloidal stability but created excessive foam. Triethanolamine-treated GNPs (TEA-GNPs) and β-Alanine-treated MWCNTs (Ala-MWCNTs) were synthesized as covalently-functionalized nanomaterials. The success of functionalization processes was confirmed through different characterization methods. Stability was found reliant on nanomaterial type, SSA, and weight concentration; and it increased up to relative concentrations of 0.876 and 0.955 for TEA-GNPs and Ala-MWCNTs, respectively. The thermal conductivity, viscosity, and density of nanofluids increased, while the specific heat decreased as weight concentration increased. The temperature was directly proportional to the thermal conductivity and inversely proportional to the viscosity, density, and specific heat. The increase in SSA produced noticeable increase in the thermal conductivity, up to 22.91% for 0.1-wt% TEA-GNPs 750. The measured thermal conductivity showed good agreement with the models of Chu et al. (2012a) for TEA-GNPs and Nan et al. (1997) for Ala-MWCNTs. For TEA-GNPs and Ala-MWCNTs, the highest increment in nanofluid viscosity was 25.69%. Since the classical viscosity models underestimated the measured values, a correlation was developed which revealed good agreement. The FPSC’s efficiency increased as the flow rate and heat flux intensity increased, and decreased as inlet fluid temperature increased. For nanofluid-based FPSC, the measured values of absorber plate temperature (AP) and tube wall temperature (TW) decreased down to 3.35% and 3.51%, respectively, with the increase in weight concentration and SSA, while the efficiency increased up to 10.53% for 0.1-wt% TEA-GNPs 750, in comparison with water. The experimental values of AP, TW, and efficiency for water very well matched the MATLAB code with maximum differences of 3.02%, 3.19%, and 3.26%, respectively. While for nanofluids, higher differences were found, up to 4.74%, 4.7%, and 13.47% for TEA-GNPs 750, respectively. The MATLAB code was considered appropriate for simulating nanofluid-based FPSCs with acceptable accuracy. Values of performance index were all > 1, and increased as weight concentration increased up to 1.104 for 0.1-wt% TEA-GNPs 750, implying higher positive effects on efficiency than negative effects on pressure drop. Accordingly, the investigated nanofluids can efficiently be used in FPSCs for enhanced energy efficiency, and the 0.1-wt% water-based TEA-GNPs 750 nanofluid was comparatively the superior one.